Analisis Daya Tampung Lahan untuk Permukiman di Wilayah Kecamatan Sawerigadi - Feryati Feryati; Hasbullah Syaf; Lukman Yunus (Universitas Halu Oleo, 2022)
Sawerigadi Subdistrict has additional residential land due to the increase in population, so the purpose of this study is to analyze the pattern of settlement growth in Sawerigadi Subdistrict, West Muna Regency, and (2) to analyze the carrying capacity of land in accordance with settlement growth in Sawerigadi District, West Muna Regency. The method used is the analysis of settlement patterns, and analysis of the suitability of settlement land. The result of this research is that the pattern of settlement growth in Sawerigadi District, West Muna Regency is spread out in each village. The population capacity in 2020 and 2030 in Sawerigadi District is generally still sufficient. Keywords: Land Capacity, SettlementKecamatan Saweigadi terjadi penambahan lahan permukiman karena bertambahnya jumlah penduduk, maka tujuan dari penelitian ini yaitu untuk mengalisis pola pertumbuhan permukiman di Kecamatan Sawerigadi Kabupaten Muna Barat, dan (2) untuk menganalisis daya dukung lahan sesuai dengan pertumbuhan permukiman di Kecamatan Sawerigadi Kabupaten Muna Barat. Metode yang digunakan yaitu analisis pola permukiman, dan analisis kesesuaian lahan permukiman. Hasil dari penelitian ini yaitu pola pertumbuhan permukiman diKecamatan Sawerigadi Kabupaten Muna Barat adalah menyebar pada masing-masing desa. Daya tampung penduduk tahun 2020 dan tahun 2030 Kecamatan Sawerigadi pada umumnya masih mencukupi.Kata Kunci : Daya Tampung, Permukiman